2017
DOI: 10.18632/aging.101201
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a-3p alters proliferation and apoptosis of meningioma cells in vitro and is directly targeting SMAD4, FRAT1 and BCL2

Abstract: Micro (mi)RNAs are short, noncoding RNAs and deregulation of miRNAs and their targets are implicated in tumor generation and progression in many cancers. Meningiomas are mostly benign, slow growing tumors of the central nervous system with a small percentage showing a malignant phenotype.Following in silico prediction of potential targets of miR-34a-3p, SMAD4, FRAT1, and BCL2 have been confirmed as targets by dual luciferase assays with co-expression of miR-34a-3p and reporter gene constructs containing the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
4
34
0
1
Order By: Relevance
“…Accumulating evidence shows that the induction of apoptosis and activation of Wnt/ β-Catenin signaling pathways dramatically suppress tumor growth, metastasis, and chemoresistance, confirming that miR-34a can regulate apoptosis through Wnt/β-catenin signaling pathways. Indeed, some studies have revealed that miR34a alters apoptosis via direct BCL2 targeting [33,34]. Our findings clearly indicate that the overexpression of miR-34a can significantly enhance EPI-induced apoptosis and Wnt/ β-Catenin signaling pathway inhibition.…”
Section: Discussionsupporting
confidence: 60%
“…Accumulating evidence shows that the induction of apoptosis and activation of Wnt/ β-Catenin signaling pathways dramatically suppress tumor growth, metastasis, and chemoresistance, confirming that miR-34a can regulate apoptosis through Wnt/β-catenin signaling pathways. Indeed, some studies have revealed that miR34a alters apoptosis via direct BCL2 targeting [33,34]. Our findings clearly indicate that the overexpression of miR-34a can significantly enhance EPI-induced apoptosis and Wnt/ β-Catenin signaling pathway inhibition.…”
Section: Discussionsupporting
confidence: 60%
“…However, one should remember that specific miRNAs can simultaneously produce competing oncogenic and tumor suppressive effects and an overall net oncogenic or net tumor-suppressive effect of miRNA may depend on the balance between miRNA-mediated upregulation or downregulation of oncogenic and tumor-suppressive pathways, the effects of the miRNA on cancer-immune system interactions and a plethora of other tumor-modifying extrinsic factors [51] . Most of upregulated miRNAs in DNMT2-silenced fibroblasts have been reported to suppress cell proliferation and promote multiple antitumor effects in different cancer models [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] . For example, miR-28-5p inhibited proliferation and migration by directly inhibiting RAP1B, a Ras-related small GTP-binding oncoprotein, in renal cell carcinoma [52] ; miR-34a-3p reduced the proliferation of meningioma cells by targeting SMAD4, FRAT1 and BCL2 [54] ; miR-30b-5p limited cell proliferation, metastasis and epithelial-to-mesenchymal transition by targeting G-protein subunit α-13 in renal cell carcinoma [55] and miR-30b-5p repressed cell proliferation by targeting DNMT3A in hepatocellular carcinoma [56] ; miR-409-3p inhibited gastric cancer cell proliferation and promoted apoptosis by targeting the transcriptional regulator PHF10 [61] and miR-409-3p suppressed breast cancer cell growth and invasion by targeting Akt1 [62] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in meningioma, miR-34a-3p was indicated to modulate cell proliferation and apoptosis by targeting BCL2. 31 Finally, the relationship among NEAT1, miR-34a-5p, and BCL2 was explored, and it was found that downregulation of NEAT1 suppressed BCL2 expression; however, this inhibitory effect was abrogated by miR-34a-5p knockdown, suggesting that NEAT1 regulated BCL2 expression by sponging miR-34a-5p.…”
Section: Discussionmentioning
confidence: 99%